Preoperative dose-escalated Intensity-Modulated Radiotherapy (IMRT) and Intraoperative Radiation Therapy (IORT) in patients with retroperitoneal soft-tissue sarcoma: final results of a clinical phase I/II trial - Seidensaal, Katharina; Dostal, Matthias; Kudak, Andreas; Jäkel, Cornelia; Meixner, Eva; Liermann, Jakob; Weykamp, Fabian; Hoegen-Saßmannshausen, Philipp; Mechtersheimer, Gunhild; Willis, Franziska; Schneider, Martin; Debus, Jürgen (Cancers, 2023)
Background: To report the final results of a prospective, one-armed, single-center phase I/II trial (NCT01566123). Methods: Between 2007 and 2017, 37 patients with primary or recurrent (N = 6) retroperitoneal sarcomas were enrolled. Treatment included preoperative IMRT of 45-50 Gy with a simultaneous integrated boost of 50-56 Gy, surgery and IORT. The primary endpoint was local control (LC) at 5 years. The most common histology was dedifferentiated liposarcoma (51%), followed by leiomyosarcoma (24%) and well-differentiated liposarcoma (14%). The majority of lesions were high-grade (FNCLCC G1: 30%, G2: 38%, G3: 27%, two missing). Five patients were excluded from LC analysis per protocol. Results: The minimum follow-up of the survivors was 62 months (median: 109; maximum 162). IORT was performed for 27 patients. Thirty-five patients underwent gross total resection; the pathological resection margin was mostly R+ (80%) and, less often, R0 (20%). We observed 10 local recurrences. The 5-year LC of the whole cohort was 59.6%. Eleven patients received a dose > 50 Gy plus IORT boost; LC was 64.8%; the difference, however, was not significant (p = 0.588). Of 37 patients, 15 were alive and 22 deceased at the time of final analysis. The 5-year OS was 59.5% (68.8% per protocol). Conclusions: The primary endpoint of a 5-year LC of 70% was not met. This might be explained by the inclusion of recurrent disease and the high rate of G3 lesions and leiomyosarcoma, which have been shown to profit less from radiotherapy. Stratification by grading and histology should be considered for future studies.
Veröffentlicht: 13. Mai 2023
Gesehen am 25.07.2023